Proinflammatory T cell polarization is already present in patients with early knee osteoarthritis - Rosshirt, Nils; Trauth, Richard; Platzer, Hadrian; Tripel, Elena; Nees, Timo A.; Lorenz, Hanns-Martin; Tretter, Theresa; Moradi, Babak (Arthritis Research & Therapy, 2021)
Investigating the pathophysiological mechanisms of early osteoarthritis (OA) is of utmost interest since this stage holds the strongest promise for therapeutic interventions. The aims of this study were to analyze if synovial inflammation is already present in early OA and to characterize the involved cell populations, by investigating synovial fluid (SF) and synovial membrane (SM) of early OA patients for the presence and polarization status of CD4 T cells.